Implementation of Data Mining at Laboratory Vocational High School Using The C4.5 Algorithm to Predict Students Major Preferences - Suherman, Nurisya Rahma; Ruuhwan, Ruuhwan; Sudiarjo, Aso (INNOVATICS: International Journal on Innovation in Research of Informatics, 2023)
Education or the learning process is the primary thing for human life. Therefore, a place for acquiring knowledge is established, which is called a school. Schools have their own levels, ranging from early childhood education to higher education institutions. When students enter high school, they are required to make decisions in choosing their majors. Accompanied by technological advancements, the issues in high school major selection can be effectively and efficiently addressed using data mining. Common issues that usually arise include lack of accuracy, precision, and requiring a significant amount of time. Hence, the issues within major selection necessitate the use of data mining, employing the C4.5 algorithm method, to determine the accuracy and precision of large datasets. This research achieved with RapidMiner the result is accuracy score of 94.44%, precision of 81.37%, and sensitivity of 74.00%. Additionally, it also generated a decision tree and with Python has an accuracy of 93% because it automatically rounds the values, so there is no significant difference between the two tools. This proves that the C4.5 algorithm produces fairly accurate performance.